(untitled) (Konferensiyalar | Conferences, 2024)
The English language has a rich vocabulary that we use when we describe our feelings, objects and phenomena of the world around us, state our requirements or try to prove something. However, an important factor in speech activity is not only what we say, but also why we say it. What determines the choice of a certain lexical unit in the communication process? Pragmatics is engaged in the search for answers to this question.